Molecular caracterization of human erythrovirus B19 strains obtained from patients with several clinical presentations in the Amazon region of Brazil - Freitas, Ronaldo Barros de (Sociedade Brasileira de Medicina Tropical, 2016)
Trabalho apresentado no Congresso da Sociedade Brasileira de Medicina Tropical, 45.; Encontro de Medicina Tropical do Cone Sul, 3.; Encontro de Medicina Tropical dos Pa?ses de L?ngua Portuguesa, 4.; Simp?sio Internacional sobre Vacinas para Leishmaniose, 2009, Recife.